(untitled) (Herald of Journalism, 2020)
This article examines the historical practice and disadvantages of cre ating an information space of the Turkic peoples. Reviewing the impact of globalization to the culture and mentality of kindred peoples, the author presents development of relations in the information sphere as effective ways to ensure information security. Also from the point of view of the author estimated the difficulties of creating a unified information space.